Clostridium difficile Associated Disease in a Neurointensive Care Unit - Tripathy, Swagata; Nair, Priya; Rothburn, Michael (Frontiers in Neurology, 2013)
ABSTRACT. BACKGROUND- Critically ill patients are at high risk for acquiring Clostridium difficile infection. The aim of this study was to investigate the prevalence, severity and outcome of Neurointensive Care Unit (NICU) acquired Clostridium difficile associated disease (CDAD). METHODS: Intensive care admission and hospital infection control databases from April 2008 to August 2010 were studied and the case notes reviewed retrospectively. Diarrhoea was classified as mild, moderate or severe based on the frequency and volume. Information on demographics, risk factors for CDAD, presentation and course of the disease was gathered. Admission diagnosis, days of NICU stay and incidence of complications were noted. RESULTS: In the time period studied, 9 out of 2212 patients (prevalence rate 0.4%) admitted to the ICU for a total of 10,825 bed days ( incidence rate 8.3 per 10,000 bed days) acquired CDAD. Median age was 55 (IQR 20-72) years. The median NICU stay was 26 (IQR 11-103) days. The median duration between ICU admission and development of CDAD was 11 (IQR 3 to 93) days. 4 patients (44%) had moderate CDAD. Concurrent infections occurred in 7 (77%) patients. The most frequently prescribed antimicrobials prior to CDAD were cephalosporins (71%). The apparent risk factors in this group included age > 65 year (22%) and antibiotics (67%) among others. One patient developed CDAD colitis. Three patients had a perceived delay in discharge from the ICU (1 to 8 days) due to their infective status. No mortality was ascribed to CDAD. CONCLUSION: The prevalence rate (0.4%) and morbidity of CDAD in the unit are low. A larger database is needed to better analyse the associated risk factors in this subgroup of patients. A possible increase in disease burden due to a delay in discharge from the ICU merits further evaluation.